Morphology, Morphometry, and Nest Structure of Tetragonula biroi (Hymenoptera: Meliponini) In Central Sulawesi - Sitti Nur Fadhilah; I Made Budiarsa; Masrianih; Fatmah Dhafir; Achmad Ramadhan; Manap Trianto (Jurnal Biologi Tropis, 2023)
Stingless bees are social bees that live in colonies. Indonesia has a variety of stingless bee species that can be identified based on morphological, morphometric and nest structure characters. This study aims to describe the morphological, morphometric and nest structure characteristics of Stingless bee Tetragonula biroi from Sigi Regency. This study used the roaming method to find samples in nature, with a purposive sampling technique. Obtained morphological, morphometry and nest structure data were analyzed using the Principal Component Analysis (PCA) method with PAST4 software. The morphological characters of the worker bee Tetragonula biroi have a dominant black body, blackish brown abdomen, antennae with 11 flagellomeres, black thorax, black hair standing on the mesoscutum and mesoscutellum, brownish black mandibles, with 5 hamuli. The most dominant character in the formation of seven groups of stingless bees in this study, namely Hamuli Number (HN), Fore Wing Length (FWL), and Length of Forewing Including Tegula (WL1). The nest entrance hole of T. biroi is elliptical in shape with a width of 7.1 cm and a height of 2.8 cm and is light brown in color. The internal structure of the nest of T. biroi consists of honey cells, pollen cells and stem cells. The existence of size differences in the same specimen and from different places, can be influenced by several environmental factors and is also a form of morphological adaptation.